THE EFFECTIVENESS OF CHRONOTHERAPY IN HYPERTENSIVE PATIENTS WITH AN INSUFFICIENT DEGREE OF SLEEP-TIME SYSTOLIC BLOOD PRESSURE DECLINE - Petrenko, O. V.; Yabluchansky, M. I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
Blood pressure (BP) circadian rhythm violation, manifested as an insufficient degree of its sleep-time relative decline, is an independent cardiovascular risk factor. The main method of the correction is chronotherapeutic approach, when at least one antihypertensive drug is taken at bedtime. However, most researchers focus on normalizing the daily profile of systolic blood pressure (SBP) and do not pay enough attention to changes in the daily profile of diastolic blood pressure (DBP) and blood pressure in general. The aim of the study was to evaluate the influence of the chronotherapeutic approach on the SBP and DBP levels and the DBP daily profile in hypertensive patients with an insufficient degree of sleep-time relative SBP decline. The study included 12 patients with arterial hypertension (AH) with an insufficient degree of sleep-time relative SBP decline. Participants were divided into two groups: group 1 included patients who take at least one antihypertensive drug at bedtime, group 2 – patients who take all antihypertensive drugs in the morning. All patients underwent 24-hour blood pressure monitoring using the computer system «Cardiosens» (KhAI Medica, Ukraine, with the oscillometric method of BP measuring) when enrolling in the study and after 3 months. The type of SBP and DBP diurnal profile, the mean values of SBP, DBP and hyperbaric indices were determined and compared between groups 1 and 2 at each visit, as well as within groups between visits. The results showed that the SBP daily profile normalization in patients with insufficient degree of sleep-time relative SBP decline from group 2 was achieved only in 11 % of cases, and in group 1 SBP and DBP daily profile normalized in 1/3 patients. In some patients from group 2 SBP and DBP daily profile converted into the overdipper type, while in group 1 overdippers did not appear at the end of the study. It was concluded that conversion of daily DBP profile to overdipper as a consequence of bedtime drug administration requires a review of the accepted treatment strategy.